Relationship between Knowledge and Attitudes of Students in Water Conservation at Madrasah Aliyah Darel Hikmah Pekanbaru Dormitory - Hardianti, Sri; Sari, Resy Kumala; Tanjung, Lailatul Syifa; Firdaus, M.; Gustriana, Etry (Journal of Engineering Science and Technology Management (JES-TM), 2023)
Water conservation is an effort to protect, use and manage water wisely to ensure the availability of sufficient water for current and future needs. This research aims to determine the relationship between students' knowledge and attitudes in water conservation at the MA Darel Hikmah Pekanbaru Dormitory. The research design used is a quantitative design using a cross-sectional approach, where researchers will look for relationships with students' knowledge and attitudes in water conservation. The independent variables (Knowledge and Attitudes) and the dependent variable (Water Conservation) in students will be assessed and measured at the same time. Data analysis in this research consisted of univariate and bivariate analysis. The research was conducted at the Madrasah Aliyah Darel Hikmah Pekanbaru Dormitory from September to October 2023. that there was a significant relationship between knowledge and water conservation at the Madrasah Aliyah Darel Hikmah Pekanbaru Dormitory with a p-value of 0.008 and there was a significant relationship between attitude and water conservation in the Dormitory Madrasah Aliyah Pekanbaru with a p-value of 0.003. It is hoped that schools can provide education to students about water conservation so that students can increase their knowledge so that it can be applied in everyday life in the dormitory.